The Power of Non-Synchronous Care: Asynchronous Telemedicine and Store-and-Forward Technologies - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
Meta Description: Explore the academic and professional landscape of Asynchronous Telemedicine ATM and Store-and-Forward SFT technologies, their applications...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Medical Ethics